Ultrastructure of silk threads of the water spider Argyroneta aquatica (Clerck, 1757) (Araneae, Cybeidae) in comparison with that of some mites - Shatrov, Andrey B.; Soldatenko, Elena V. (Frontiers in Arachnid Science, 2024)
Silk of the water spider Argyroneta aquatica (Clerck, 1757) was obtained in the laboratory in the form of a capturing web irrespective of the formation of a diving bell and egg cocoon. Silk threads were examined by light microscopy, scanning (SEM), and transmission electron microscopy (TEM) as well as by atomic force (AFM) microscopy. Based on the diameter and internal organization, the silk threads have been divided into five types—a-, b-, c-, d-, and e-types interlaced freely in the thread bundles taken for examinations. Threads of all types are infinitely long, non-branched, round in shape, uniform in width through their course, and rarely found to be ruptured. Threads of the a-type are mostly straight, up to 1,000 nm in diameter, and composed of a fibrillary wall enveloping an electron-dense vacuolated core, which may be occasionally absent. The wall may also become lost, leaving a single core substance surrounded by a slightly wrinkled double membrane. Threads of the b-, c-, and d-types are organized nearly identical, being composed of a fine granular electron-light uniform material enveloped by a fine membrane. The diameter of these threads varies from max. 500 nm in the b-type and 120 nm in the c-type to around 50 nm in the d-type. Threads of these types are more convoluted and more numerous than threads of the a-type. Threads of the last kind, the e-type, occur rarely and are significantly larger with a diameter of around 3.5–4.5 µm. They possess the layered membranous wall surrounding a uniformly dense core. The silk of the water mites Limnochares aquatica (L., 1758) and Limnesia maculata (O.F. Müller, 1776) is composed of threads of only one type that closely corresponded to the a-type threads of A. aquatica. Conversely, the silk of the two-spotted spider mite Tetranychus urticae (C.L. Koch, 1836) consists of threads highly correlated with the d-type threads of A. aquatica. This finding shows that in different phylogenetic lineages of arachnids, the mechanisms of silk production are quite similar.